1994
DOI: 10.1093/oxfordjournals.eurheartj.a060491
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of ventricular fibrillation by atrial fibrillation

Abstract: We report the case of a patient who developed spontaneously a ventricular fibrillation during atrial fibrillation, 8 min after a perfusion of isoproterenol was stopped. Two mechanisms could explain the ventricular arrhythmia: silent ischaemia and a long-short cycle sequence just before ventricular fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several mechanisms by which ventricular arrhythmia could be directly induced by AF with a rapid ventricular response have been proposed including silent myocardial ischemia [15,19,20], enhanced atrioventricular node conduction [19], and short-long short ventricular cycle sequences followed by ventricular tachycardia [14,15]. Patients with HCM are more susceptible to myocardial ischemia because of small vessel abnormalities, such as thickened walls and limited luminal area [2,29,30], and this has been regarded as one of the most essential pathophysiological features that promotes ischemic damage to the ventricular myocardium [29,31,32] and influences the outcome of HCM [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms by which ventricular arrhythmia could be directly induced by AF with a rapid ventricular response have been proposed including silent myocardial ischemia [15,19,20], enhanced atrioventricular node conduction [19], and short-long short ventricular cycle sequences followed by ventricular tachycardia [14,15]. Patients with HCM are more susceptible to myocardial ischemia because of small vessel abnormalities, such as thickened walls and limited luminal area [2,29,30], and this has been regarded as one of the most essential pathophysiological features that promotes ischemic damage to the ventricular myocardium [29,31,32] and influences the outcome of HCM [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical cohort studies have shown that AF is associated with a substantial increase in the overall risk of HCM-related death, but not sudden death [8,13]. On the other hand, there have been several reports of AF triggering life-threatening ventricular arrhythmias [14][15][16][17][18][19][20]. It thus remains controversial whether AF is associated with sudden death in patients with HCM.…”
Section: Introductionmentioning
confidence: 99%